Report on the 18th International Scientific Conference in the Series “Humanistic Ecology” “Contemporary Environmental Dilemmas: Interdisciplinary Approaches” (Bratislava, 26-27 September 2024) - Klimska, Agnieszka (Studia Ecologiae et Bioethicae, 2025)
This report summarises the 18th ISC in the "Humanistic Ecology" series, titled "Contemporary Environmental Dilemmas: Interdisciplinary Approaches" (Bratislava, 26-27 September 2024) which offered a multifaceted examination of the civilisation crisis by exploring the intricate relationship between humanity and nature. The conference brought together experts from the natural sciences, humanities, and social sciences, facilitating the exchange of ideas and the presentation of diverse scholarly perspectives. The papers addressed topics ranging from evolutionary and geological contexts to legal-economic issues and theological reflections, emphasising the need for holistic strategies aimed at achieving sustainable development. The report also highlights necessity for ongoing reflection and prompt adaptive measures in response to rapidly evolving environmental challenges.